Politica agricolă românească şi perspectiva aderării la Uniunea Europeană - Dragoș Negrescu (Romanian Journal of European Affairs, 2002)
The paper attempts to systematically explore, first, the rationales for supporting the agricultural sector in Romania and, second, the extent to which the preparation for accession calls for the dispensation of such aids. The author concludes that, following a brief period of rationalization, both the scope and, even more so, the modalities of supporting the agricultural sector are prone to lead to perverse effects, while not facilitating in any meaningful way the country’s eventual accession to the European Union. Refuting with hard facts the often repeated assertion that domestic farmers are deprived of protection against competing imports, the paper highlights some very questionable features of Romania’s trade policy in the agricultural area and calls for a different approach, centered on reducing barriers facing imports destined to the local market in exchange for improved access of Romanian exports to foreign markets.